Management consulting winning: internationalization analysis: European market - Ferreira, Inês Pinto (2016)
A few decades ago, global management consulting was considered to be one of the most attractive industries due to its abnormal high profit margins and above-average growth rates. However, after the dot-com bubble in 2000 and the last global financial crisis, firms folded and growth rates declined sharply. In an attempt to overcome the uncertainty and information volatility, internationalization is commonly cited as a good strategy. WMC, a Portuguese SME founded in 2012, has now decided to expand its management consulting services. Therefore, a scoring model was created to assess selected European countries’ attractiveness taking into consideration macro and microeconomic data. Results show that Spain is the best option at the moment, mainly because it is where the company has the larger number of projects already developed and is more likely to leverage its network.